Hemorrhagic and thrombotic complications in pregnancy: diagnosis, prevention, and treatment - Alvarado, Carlos S. (2023)
Bleeding and venous thromboembolism (VTE) are among the five most common causes of morbidity and mortality in pregnant women worldwide. This review describes the current evaluation and management of the obstetric causes of postpartum hemorrhage (PPH) – the leading cause of maternal mortality in our country in recent years prior to the pandemic, as well as the diagnosis and management of hematologic conditions which can cause or worsen PPH, such as autoimmune thrombocytopenia, von Willebrand disease, and thrombotic microangiopathies. It also describes the role of the antiphospholipid syndrome and inherited thrombophilias as predisposing factors of recurrent pregnancy loses and VTE, and the current recommendations for the prevention of both complications. One of the objectives of this Review is to emphasize the importance of a collaborative multidisciplinary approach for the successful management of the obstetric and hematologic complications herein described.